Constipation prevalence and perceptions: Comparison of children and adolescents with ASD and other developmental-behavioral disorders. (February 2021) - Cuffman, Carrie; Burkhart, Kimberly
Highlights: Patients with ASD have higher lifetime risk of constipation. Patients with ASD have increased medication use for constipation. Parent and child reports of child constipation frequently differ. Rome IV criteria for constipation identify more constipation vs a single question. Abstract: Background: Few studies have compared youth constipation in autism spectrum disorder (ASD) to constipation in other developmental-behavioral (DB) disorders. Methods: Children and caregivers presenting to a DB pediatrics and psychology clinic completed written questionnaires on constipation. Comparison groups were ASD vs without ASD and caregiver vs child responses. Binary logistic regression were conducted to compare categorical variables. Results: Caregivers of 169 toilet trained children and 26 non-toilet trained children completed the survey; 30 % of the toilet trained and 62 % of the non-toilet trained children had ASD. 88 toilet trained children completed the survey. Based on caregiver response, toilet trained youth with ASD were more likely to have been constipated in the past and to currently or previously taken medication to manage constipation. In both the total toilet trained and non-toilet trained sample, more caregivers endorsed their child meeting Rome IV criteria for functional constipation than endorsed current constipation. 37 % of parent/child pairs disagreed on whether the child met the Rome IV criteria. Caregivers of toilet trained youth with ASD were more likely to endorse specific barriers and impairment due to managing constipation in comparison to caregivers of youth without ASD. Conclusions: Children with ASD may be at a higher lifetime risk of constipation and of needing medication compared to children with other DB disorders. Providers should use thorough questions to identify constipation and gather information from both caregiver and child when possible. Clinicians should consider targeting behavioral treatment recommendations to perceived caregiver concerns.